2020
DOI: 10.26636/jtit.2020.143520
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Compact Microstrip Antenna Using the Machine Learning Approach

Abstract: This paper presents how machine learning techniques may be applied in the process of designing a compact dual-band H-shaped rectangular microstrip antenna (RMSA) operating in 0.75–2.20 GHz and 3.0–3.44 GHz frequency ranges. In the design process, the same dimensions of upper and lower notches are incorporated, with the centered position right in the middle. Notch length and width are verified for investigating the antenna. An artificial neural network (ANN) model is developed from the simulated dataset, and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The study showed significantly faster performance (almost three times faster via ML) while conserving the accuracy of the coupling coefficient. NN has provided over 99% accuracy towards [54] synthesizing an H-shaped rectangular microstrip antenna (RMSA). However, studies have shown that the Radial Basis Functions (RBF) of ANN are best suitable for evaluating the resonant frequency of rectangular microstrip patch antennae [55].…”
Section: Design Optimization and Synthesismentioning
confidence: 99%
“…The study showed significantly faster performance (almost three times faster via ML) while conserving the accuracy of the coupling coefficient. NN has provided over 99% accuracy towards [54] synthesizing an H-shaped rectangular microstrip antenna (RMSA). However, studies have shown that the Radial Basis Functions (RBF) of ANN are best suitable for evaluating the resonant frequency of rectangular microstrip patch antennae [55].…”
Section: Design Optimization and Synthesismentioning
confidence: 99%